The Influence of Organizational Culture, Intrinsic Motivation, and Organizational Citizenship Behavior on Employee Performance - Igantius Soni Kurniawan Soni Kurniawan; Eni Cahyani; Rohmawan Adi Pratama; Lusia Tria Hatmanti Hutami; Shifa Megarani (Relevance: Journal of Management and Business, 2023)
This study aims to analyze the influence of organizational culture, intrinsic motivation, and OCB on employee performance at Peci Abbas Group SMEs. This study is a quantitative study whose data was taken at the MSME Peci Abbas Group on a census of 51 employees. The data were processed through reliability validity test, classical assumption test, and multiple linear regression analysis using SPSS 23 software. The results showed that organizational culture had no significant effect on employee performance, intrinsic motivation had no significant effect on employee performance, OCB had a significant positive effect on employee performance. The results have implications for organizational leaders to maintain and improve OCB when making policies to improve employee performance